The Role of the Organization of Islamic Cooperation in Combating Islamophobia the Post-Paris Attacks 13 November 2015 - Indri Rahayu; Muhaimin Zulhair Achsin (PT ARRUS Intelektual Indonesia, 2023)
The Paris attacks of 13 November 2015 have caused Islamophobic acts to increase. The Muslim community in France experiences verbal and physical discrimination and violence, hatred, and acts of religious blasphemy have tripled. Islamophobia following the Paris attacks was the highest among European countries. This ultimately encouraged the Organization of Islamic Cooperation (OIC) to become involved in activities to combat Islamophobia. This article examines the role of the OIC in combating Islamophobia in France after the Paris attacks by using its work in the international world. The study was carried out qualitatively using Clive Archer's concept of international organizations. The research found that the OIC plays a role in fighting Islamophobia as an instrument, forum, and actor. The OIC plays an influential role in fighting Islamophobia through various strategies to eliminate discrimination against Muslims worldwide by collaborating with several internal and external parties. Of the three roles that the OIC has, the most dominant role in combating Islamophobia is the OIC's role as an international actor who can pioneer in pioneering policies and making decisions related to combating Islamophobia while adhering to international legal standards for fighting Islamophobia. The OIC succeeded in establishing resolution No.32/44 POL regarding combating Islamophobia, eliminating hatred and discrimination against Islam, and a media strategy policy to mobilize a campaign to develop peace and stop Islamophobia.